2013
DOI: 10.5194/amt-6-3271-2013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an aerodynamic lens for transmitting particles greater than 1 micrometer in diameter into the Aerodyne aerosol mass spectrometer

Abstract: Abstract.We have designed and characterized a new inlet and aerodynamic lens for the Aerodyne aerosol mass spectrometer (AMS) that transmits particles between 80 nm and more than 3 µm in vacuum aerodynamic diameter. The design of the inlet and lens was optimized with computational fluid dynamics (CFD) modeling of particle trajectories. Major changes include a redesigned critical orifice holder and valve assembly, addition of a relaxation chamber behind the critical orifice, and a higher lens operating pressure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 18 publications
1
73
0
Order By: Relevance
“…It is well established that an aerodynamic lens can achieve an efficiency close to unity for the size range under examination here (20-600 nm) (Huffman et al, 2005;Williams et al, 2013); therefore, although the lens is uncharacterised, we assumed E 600 nm Lens = 1. It was observed that the vast majority of PSL particles that produced an optical trigger also produced a mass spectrum so that E 600 nm Hit ≈ 1.…”
Section: Instrument Performance Measurementsmentioning
confidence: 99%
“…It is well established that an aerodynamic lens can achieve an efficiency close to unity for the size range under examination here (20-600 nm) (Huffman et al, 2005;Williams et al, 2013); therefore, although the lens is uncharacterised, we assumed E 600 nm Lens = 1. It was observed that the vast majority of PSL particles that produced an optical trigger also produced a mass spectrum so that E 600 nm Hit ≈ 1.…”
Section: Instrument Performance Measurementsmentioning
confidence: 99%
“…The version of the instrument used in this study features an aerodynamic lens inlet (model LP2.5 Aeromegt GmbH) for transmission of particles approximately 0.07-2.5 µm in diameter that is similar in design to the high-pressure lens (HPL) described by Williams et al (2013). Divergence of the particle beam is size and shape dependent (Jayne et al, 2000), resulting in a morphological dependence on the fraction of particles that reaches the ionisation region (Huffman et al, 2005), an effect that is particularly important for mea- Laser desorption ionisation takes place in a high vacuum (< 1 × 10 −6 mbar) region some 230 mm from the aerodynamic lens exit, where particles interact with a 8 ns pulse of 193 nm radiation that is fired co-axial but counter-propagate to the particle beam.…”
Section: Laap-tof Single-particle Mass Spectrometermentioning
confidence: 99%
“…The hourly near-surface CO, SO (Williams et al, 2013). The positive matrix factorization (PMF) technique is utilized with constraints implemented in SoFi (Canonaco et al, 2013) to analyze the sources of OA and five components are separated by their mass spectra and time series.…”
Section: Pollutant Measurementsmentioning
confidence: 99%